Magnetic Resonance Imaging Role in Metastatic Liver Disease - Santana, Tomás; Laert, José; Lupi Manso, Nuno; Felipe Luersen, Gustavo; Pedro Matos, António (Gazeta Médica, 2024)
The objective of this study is to provide a comprehensive overview of the utilization of magnetic resonance imaging (MRI) in the identification, characterization, and monitoring of liver metastatic disease, in contrast to alternative imaging modalities, through a bibliographical review and illustrative examples from the author’s clinical practice. The advantages of MRI in this specific context will be explored, emphasizing the utility of hepatospecific contrast agents and the limitations associated with alternative imaging modalities. A comparative analysis of these methods shows that MRI is the most sensitive and specific modality, even more so when using hepatospecific contrast agents, proving to have cost-effectiveness benefits in patient management. It is the authors’ opinion that, provided the technique is available, oncological patient staging where hepatic metastatic disease is a concern should include an abdominal MRI, if possible, with hepatospecific contrast.